2011
DOI: 10.1590/s1415-47572011000400017
|View full text |Cite
|
Sign up to set email alerts
|

Expressed sequence tag analysis of khat (Catha edulis) provides a putative molecular biochemical basis for the biosynthesis of phenylpropylamino alkaloids

Abstract: Khat (Catha edulis Forsk.) is a flowering perennial shrub cultivated for its neurostimulant properties resulting mainly from the occurrence of (S)-cathinone in young leaves. The biosynthesis of (S)-cathinone and the related phenylpropylamino alkaloids (1S,2S)-cathine and (1R,2S)-norephedrine is not well characterized in plants. We prepared a cDNA library from young khat leaves and sequenced 4,896 random clones, generating an expressed sequence tag (EST) library of 3,293 unigenes. Putative functions were assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…2 , S2 Fig .). The GO analysis results for CED-Trinity are very similar to those reported for a Sanger sequencing-based khat cDNA library [ 14 ]. This finding is not surprising, as source tissue was the same in both cases.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…2 , S2 Fig .). The GO analysis results for CED-Trinity are very similar to those reported for a Sanger sequencing-based khat cDNA library [ 14 ]. This finding is not surprising, as source tissue was the same in both cases.…”
Section: Resultssupporting
confidence: 70%
“…In some cases, more than one enzyme is known to catalyze a particular step; for example, dehydrogenation of benzaldehyde to benzoic acid may occur in Arabidopsis seeds through aldehyde oxidase-4 (AtAAO4) [ 25 ] or via benzaldehyde dehydrogenase in snapdragon (AmBALDH) [ 26 ]. Previous analysis of a modest (3,293 unigenes) khat transcriptomic library indicated that only a AmBALDH homologue was present, suggesting a pathway more similar to snapdragon petals than seeds of Arabidopsis [ 14 ]. The more extensive sequencing performed in this study revealed the presence of both AtAAO4 (CeBDH1–1) and AmBALDH (CeBDH2–1, 2–3, 2–4) homologues in CED-Trinity ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, highest amount of alkaloids was found when fresh material was freeze‐dried (Laussmann and Meier‐Giebing, ). To shed light on the biosynthesis of khat alkaloids, a cDNA library from young khat leaves was prepared, and candidate genes had been identified that are potentially involved in various stages of the biosynthesis (Hagel et al, ).…”
Section: Chemical Constituents Of Khatmentioning
confidence: 99%
“…Since N-methylation of phenylpropylamino alkaloids does not occur in khat, oxazolidine or oxazolidone formation might be a possible stabilization mode of phenylpropylamino alkaloids in khat tissues. With the advent of better genomic, metabolomic, and transcriptomic platforms to study alkaloid metabolism [26], we will gain much of the needed knowledge to elucidate the biosynthetic pathways to phenylpropylamino alkaloids and their derivatives. At present, we can only speculate about the ecological roles of phenylpropylamino alkaloids and their oxazolidine derivatives in the plants.…”
mentioning
confidence: 99%